Proceedings of the 4th Asian Education Symposium (AES 2019) 2020
DOI: 10.2991/assehr.k.200513.061
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial Self-Efficacy: Training, Observation, Internships, and the Business Plans

Abstract: A person's confidence to succeed in running a business that will be carried out is called Entrepreneurial selfefficacy Entrepreneurial self-efficacy is not an innate ability, but can be generated by motivating students to become entrepreneurs. The effort to grow self-efficacy for entrepreneurship was carried out to 35 Kanjuruhan University Malang students. The activity is entrepreneurship training, visitsin SMEs, internship activities in SMEs, and training in preparing a business plan. The purpose of this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
(12 reference statements)
0
4
0
Order By: Relevance
“…Outside of the Brush (2014) contextual framework, students often brought up their jobs and internships as experiences that have enhanced their EM through communication skills. As stated in the literature, participation in outside job experiences has been shown to improve confidence, sense of community and belonging, and leadership (Andayani et al., 2020; Chen et al., 2017; Ramsgaard & Østergaard, 2018). These results can be linked to the communication code, as many of the interviewees discussed improved confidence in themselves in both their individual and teamwork abilities.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Outside of the Brush (2014) contextual framework, students often brought up their jobs and internships as experiences that have enhanced their EM through communication skills. As stated in the literature, participation in outside job experiences has been shown to improve confidence, sense of community and belonging, and leadership (Andayani et al., 2020; Chen et al., 2017; Ramsgaard & Østergaard, 2018). These results can be linked to the communication code, as many of the interviewees discussed improved confidence in themselves in both their individual and teamwork abilities.…”
Section: Discussionmentioning
confidence: 97%
“…They found that when students used their entrepreneurial learning approach throughout their internships, they were able to identify opportunities easily, felt as though they belonged in the workforce, and had a better understanding of their learning outcomes (Ramsgaard & Østergaard, 2018). Many of the traits developed in students through internship and work experiences relate to their self-confidence in their work, as well as their interest in entrepreneurship, which in turn has been shown to be related to the development of their entrepreneurial self-efficacy (Andayani et al., 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Marullo et al, (2018) conducted the study on the nascent entrepreneurs and found that, the failure of start-ups is normally associated with team's inability to manage their internal resources (human capital, technology, financial). Hence, improving the potential entrepreneurs' self-efficacy through training can be beneficial for the growth and development of entrepreneurship (Andayani et al, 2020). Hence, the following hypothesis is proposed.…”
Section: Managerial Skills and Economic Growth Of Pakistanmentioning
confidence: 99%
“…Several studies have examined the role of TVET in economic growth and factors that impact entrepreneurial self-efficacy (ESE), and further, shed light to ascertain whether visiting the entrepreneurship-related industry and designing a business plan influence entrepreneurial self-efficacy. The studies recommended that lectures, and conducting training on business plan making should be based on the level of training participants, and as such enhance the entrepreneurial capacity (Akpoyibo, 2015, Abu-Naser et al, 2017Al Shobaki et al, 2018;Andayani et al, 2020).…”
Section: Entrepreneurial Self-efficacy and Role Of Technical Educatio...mentioning
confidence: 99%